PERSEPSI WISATAWAN TERHADAP FASILITAS TAMAN WISATA BATU ENAM KABUPATEN ROKAN HILIR - ", Arapandra; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research is to know how the tourits perception of the standardization expediency facility at six stone park in bagansiapiapi city rokan hilir district. This research is used descriptive quantitative methods. There were 100 sample of that people is taken for accidental sampling. The data collection techniques in this research used observation, interview, and quesionnaires. The likert scale was used to measure the intervals in quantitative data. This research used R.G Soekadijo (1996) theory. This theory divides the standart 3 categories: space perspective and interest, color and architectural perspektive, completeness and care. The result of the research shows that the tourits perception of the facility at six stone park includedin both category, this is due to high value on space perspective and interest, color and architectural perspective. But the low value given to completeness and care because it has never been done to the facility in six sitone tourist park.     Keywords: perception, tourist park and standardization expediency facility.